2000
DOI: 10.3758/bf03214356
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of irrelevant speech on memory

Abstract: The feature model (Nairne, 1990) is extended to account for the effects of irrelevant speech and concomitant interactions in immediate serial recall. In the feature model, both articulatory suppression and irrelevant speech are seen as adding noise to the memory representation, the difference being that articulatory suppression diverts more resources than does irrelevant speech. The addition of noise impairs recall because it reduces the probability of successful redintegration. When a competitor is incorrectl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
393
7
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(428 citation statements)
references
References 80 publications
21
393
7
1
Order By: Relevance
“…This suggests that semantic distraction effects in semantic fluency are unlikely to be due to depletion of a generalpurpose executive resource (cf. Buchner & Erdfelder, 2005;Cowan, 1995;Elliott, 2002; see also Neath, 2000). Rather, the effects seem to arise because of the disruption of processes related to the semantic activation of candidate items.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that semantic distraction effects in semantic fluency are unlikely to be due to depletion of a generalpurpose executive resource (cf. Buchner & Erdfelder, 2005;Cowan, 1995;Elliott, 2002; see also Neath, 2000). Rather, the effects seem to arise because of the disruption of processes related to the semantic activation of candidate items.…”
Section: Resultsmentioning
confidence: 99%
“…No evidence has been found that pinpoints the locus of individual differences in susceptibility unambiguously. This is disappointing because any factor influencing the extent to which an individual suffers from the irrelevant sound effect must, of necessity, be a mechanism governing the very existence of the effect, an issue that is still a matter of some controversy (Baddeley, 1986;Cowan, 1995;Jones et al, 1996;Neath, 2000). The current set of data can, however, be put alongside those of Ellermeier and Zimmer (1997) and Neath et al (2003) in ruling out one possible explanation of the effect.…”
Section: Implications For the Irrelevant Sound Effectmentioning
confidence: 99%
“…Findings from research into the effects of irrelevant sound have informed a number of contemporary models of memory function, including the working memory model of Baddeley (1986), the object-oriented episodic record model of Jones (1993), and the feature model of Neath and Nairne (Nairne, 1990;Neath & Nairne, 1995;Neath, 2000). All of these models have enjoyed some degree of support from research into the irrelevant sound effect, but despite the ongoing high level of research into the phenomenon, there are a number of questions yet to be answered.…”
mentioning
confidence: 99%
“…Jones (Jones, 1993;Jones & Tremblay, 2000) suggests the sound disrupts cues to serial order in multi-modal short-term memory system. Neath (Neath, 2000) gives an account in terms of the Nairne (Nairne, 1990) feature model, with the irrelevant sound disrupting the features that underpin recall. Baddeley interprets the effect in terms of the phonological loop component of working memory, while leaving the precise mechanism of disruption unspecified (Baddeley, 2000;Larsen & Baddeley, in press).…”
Section: Introductionmentioning
confidence: 99%